Bank capital buffer and portfolio risk: The influence of business cycle and revenue diversification - Shim, Jeungbo (Journal of Banking & Finance, 2013)
The relationship between macroeconomic developments and bank capital buffer and portfolio risk adjustments is relevant to assess the efficacy of newly created countercyclical buffer requirements. Using the U.S. bank holding company data over the period 1992:Q1–2011:Q3, we find a negative relationship between the business cycle and capital buffer. Our results offer some support for the Basel III agreements that countercyclical capital buffer in the banking sector is necessary to help the performance of the real economy during recessions. We find a robust evidence of inverse relationship between business cycle and bank default risk. Our analysis provides evidence of diversification benefits. The probability of insolvency risk decreases for diversified banks and banks with high revenue diversity achieve capital savings.